2005
DOI: 10.1177/1094428104272182
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Reasoning Measure for Aggression

Abstract: This article describes a new approach for assessing cognitive precursors to aggression. Referred to as the Conditional Reasoning Measurement System, this procedure focuses on how people solve what on the surface appear to be traditional inductive reasoning problems. The true intent of the problems is to determine if solutions based on implicit biases (i.e., biases that operate below the surface of consciousness) are logically attractive to a respondent. The authors focus on the types of implicit biases that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
258
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(273 citation statements)
references
References 56 publications
9
258
3
3
Order By: Relevance
“…Todorov & Bargh, 2002;James et al, 2005;Ireland & Birch, 2013;Bluemke, Friedrich & Zumbach, 2009;Frost, Ko & James, 2007). The findings have also extended to prison samples where the more impulsive implicit processing, rather than the more cognitively effortful processing, is thought to relate to increased aggression tendencies (Ireland & Adams, 2015).…”
mentioning
confidence: 76%
“…Todorov & Bargh, 2002;James et al, 2005;Ireland & Birch, 2013;Bluemke, Friedrich & Zumbach, 2009;Frost, Ko & James, 2007). The findings have also extended to prison samples where the more impulsive implicit processing, rather than the more cognitively effortful processing, is thought to relate to increased aggression tendencies (Ireland & Adams, 2015).…”
mentioning
confidence: 76%
“…We argue that the balance between psychopathic tendencies and the drive hold a positive view of the self as a successful individual may be maintained through ''defense mechanisms'' (Cramer 1998(Cramer , 2000 that allow the simultaneous expression of negative and positive aspects of the self. This approach has previously been used in the context of aggressive individuals, who must similarly balance negative drives (i.e., aggression) with the drive for positive self-worth (see James et al 2005). As it pertains to psychopathy, such defense mechanisms, in the form of moral disengagement, may allow psychopaths to simultaneously satisfy their drive for normviolating behavior, while maintaining a positive view of the self as a successful individual.…”
Section: The Role Of Moral Disengagementmentioning
confidence: 99%
“…The measure is based on a variation of procedures suggested by James (2005), LeBreton, Barksdale, Robin, and James (2007), and Mumford, Connelly, Helton, Van Doorn, and Osborn (2002). These studies indicated that personality may be determined via examination of complex problems that allow for expression of differential beliefs.…”
Section: Identifying Leader Typesmentioning
confidence: 99%